Nanomedicine in Lung Cancer Immunotherapy - Doroudian, Mohammad; Zanganeh, Saba; Abbasgholinejad, Elham; Donnelly, Seamas C. (Frontiers in Bioengineering and Biotechnology, 2023)
Lung cancer is the major cause of cancer death worldwide. Cancer immunotherapy has been introduced as a promising and effective treatment that can improve the immune system’s ability to eliminate cancer cells and help establish immunological memory. Nanoparticles can contribute to the rapidly evolving field of immunotherapy by simultaneously delivering a variety of immunological agents to the target site and tumor microenvironment. Nano drug delivery systems can precisely target biological pathways and be implemented to reprogram or regulate immune responses. Numerous investigations have been conducted to employ different types of nanoparticles for immunotherapy of lung cancer. Nano-based immunotherapy adds a strong tool to the diverse collection of cancer therapies. This review briefly summarizes the remarkable potential opportunities for nanoparticles in lung cancer immunotherapy and its challenges.